Event completion: a test case for theories of reference in memory. - Murez, Michael; Strickland, Brent (Synthese, 2024)
Although we encounter objects from a particular perspective, what we perceive and remember are typically whole objects. In 'amodal completion' our mind automatically fills in objects' spatially occluded parts, and our memory then often discards information about the orientation from which the objects were perceived. An analogous phenomenon of 'event completion' has been demonstrated, which may be understood as the mind automatically filling in temporally occluded parts of events. Exemplifying typical experiments in this paradigm, Strickland and Keil (Strickland and Keil, Cognition 121:409–415, 2011) showed participants videos depicting a causal event (e.g., someone kicking a ball), which was edited so that a crucial part was missing (e.g., the moment of contact between foot and ball). Subjects were more likely to falsely remember having seen the moment of contact if (and only if) it was strongly implied by subsequent footage. We use this phenomenon of event completion as a test case for comparing different theories of reference in memory. We argue that event completion puts pressure on both pure causal and pure descriptive theories of reference, and favors more nuanced hybrids of causal and descriptive theories, which integrate insights from cognitive and epistemic approaches.